he capital and application of results in agrarian processing companies: praxis and proposals lege ferenda - Juana Isabel Genovart Balaguer (AECOOP Escuela de Estudios Cooperativos, 2015)
The legal framework for Agrarian Processing Companies (SAT) does not regulate legal and economic aspects of these companies in any great detail, allowing a wide margin to the will of the partners, those who will shape in the bylaws. This lack of regulation or granting of freedom, as desired interpret, around the economic system of this form of company, has led to the existence of SAT very different depending on their particular bargaining solution embodied in the statutes. This motivates the existence of SAT taking as an economic-financial model of reference of cooperatives, others have eyes on the economic and financial structure of corporations and limited partnerships, and a third group, which contain only specific rules regarding its economic system and on occasion have been described as economically very basic societies. This paper analyzes the real configuration presented in these organizations and as will be seen, sometimes leads to a hybrid entities. To verify the reality of the SAT, we analyze all the statutes and founding minutes of the SAT enrolled in Baleares. So we have known the true statutory regulation of political, economic and social aspects, the legislature left to the discretion of its partners. On the above, we will present proposals to improve the regulation of these entities.